Capital Structure Theory and REIT Security Offerings - HOWE, JOHN S.; SHILLING, JAMES D. (Journal of Finance, 1988)
ABSTRACT In this paper, we examine the stock price reactions to announcements of new security offerings by Real Estate Investment Trusts (REITs). REITs offer a unique setting in which to study these events because they do not pay taxes at the firm level. Theory suggests that the net tax gain to corporate borrowing is unambiguously negative for a REIT. Contrary to some recent studies, however, we find a positive stock price reaction to debt offerings, while the negative equity‐issuance effect is preserved. Further empirical evidence lends support to signalling as the explanation for the positive significant debt‐issuance effect.